Identification of Adhesins in Plant Beneficial Rhizobacteria Bacillus velezensis SQR9 and Their Effect on Root Colonization - Huang, Rong; Feng, Haichao; Xu, Zhihui; Zhang, Nan; Liu, Yunpeng; Shao, Jiahui; Shen, Qirong; Zhang, Ruifu (Molecular plant-microbe interactions, 2022)
Probiotic Bacillus colonization of plant root surfaces has been reported to improve its beneficial effect. Chemotaxis, adhesion, aggregation, and biofilm formation are the four steps of root colonization by plant growth–promoting rhizobacteria (PGPRs). Compared with the other three well-studied processes, adhesion of PGPRs is less known. In this study, using mutant strains deleted for potential adhesin genes in PGPR strain Bacillus velezensis SQR9, adherence to both cucumber root surface and abiotic surface by those strains was evaluated. Results showed that deletion mutations ΔlytB, ΔV529_10500, ΔfliD, ΔyhaN, and ΔsacB reduced the adhesion to root surfaces, while, among them, only ΔfliD had significant defects in adhesion to abiotic surfaces (glass and polystyrene). In addition, B. velevzensis SQR9 mutants defective in adhesion to root surfaces showed a deficiency in rhizosphere colonization. Among the encoded proteins, FliD and YhaN played vital roles in root adhesion. This research systematically explored the potential adhesins in a well-studied PGPR strain and also indicated that adhesion progress was required for root colonization, which will help to enhance rhizosphere colonization and beneficial function of PGPRs in agricultural production. [Formula: see text] Copyright © 2021 The Author(s). This is an open access article distributed under the CC BY-NC-ND 4.0 International license .